ANALISIS PERAN STAKEHOLDERS DALAM PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA - David Adi Susilo; Retno Sunu Astuti; Budi Puspo Priyadi (NATAPRAJA, 2019)
This study aims to determine the role of stakeholders in the regulation and guidance of street vendors in Tlogosari Kulon Village, Pedurungan District, Semarang City and to identify inhibiting factors in the implementation and management of street vendors. This research method uses descriptive qualitative, by collecting observational data, interviews, library research and documentation, interview techniques conducted to several informants including the Semarang City Trade Office, Semarang City Police Satpol, Tlogosari Kulon Urban Village, Street Vendors (PKL) in the Kelurahan Tlogosari Kulon and the Tlogosari Kulon Community. The results showed that the role of the Semarang City Trade Office as a policy creator, coordinating with other agencies and PKL Tlogosari Kulon, as well as building PKL Shelter Suryokusumo Market. The role of the community as an implementator is to provide active input in the regulation or preparation of public policies in the regulation and guidance of street vendors, both directly and indirectly. While the inhibiting factors are lack of effective communication, lack of human resources and a fragmented bureaucratic structure.